Jemisimiham Jehu Appiah - Botchway, De-Valera N.Y.M. (Social sciences and missions, 2017)
In the Gold Coast, now Ghana, J.W.E. Appiah, a teacher-catechist, left the missionary-founded Methodist Church for opposing his Afrocentric healing and preaching activities and founded the Musama Disco Christo Church in the 1920s. He then took on the prophetic name Jemisimiham Jehu Appiah. He wrote his philosophies to validate an Afrocentric church in the indigenous Fante language. His Church, an African anti-colonialist/anti-colonial establishment, is alive; yet his untranslated writings have remained in obscurity. This study provides a biographical view of Appiah. It translates his writings and interrogates their inner logic as liberation theology that rationalised the salvaging of certain indigenous mores through Afrocentric Christianity to promote a Black Nationalist cultural awareness.